Geomorphometry and Statistical Analyses of Landslides Triggered by the 2015 Mw 7.8 Gorkha Earthquake and the Mw 7.3 Aftershock, Nepal - Tian, Yingying; Owen, Lewis A.; Xu, Chong; Shen, Lingling; Zhou, Qing; Figueiredo, Paula M. (Frontiers in Earth Science, 2020)
The 2015 Mw 7.8 Gorkha earthquake in Nepal and its Mw 7.3 aftershock triggered at least 22,914 landslides larger than 500 m2 in area and with lengths and widths longer than 20 m. Amongst these landslides, 2,059 had areas >10,000 m2. Analyses of the landslide geometry, using length (L), width (W), height (H, from the crown to toe), reach angle (arctan value of H/L), and aspect ratio (L/W), show that most of the landslides have aspect ratios of 1.6–3.6 and reach angles of 35–45°. The fitting relationship between H and L is H=0.87L-11.11. The steep topography is likely a main factor that controls the landslide runout and planar shape. Using the aspect ratio, these landslides are divided into three geomorphometric categories: LS1 (L/W≤2); LS2 (2